Pancytopenia due to Restrictive Food Intake in an Autistic Adult. (November 2022) - Lowe, Danielle; Barrett, Christian; Shepherd, Chelsea; Charles, Jane; Kalivas, Benjamin
Autism spectrum disorder (ASD) is a neuro-behavioral syndrome that develops in childhood and can be comorbid with restrictive and avoidant food intake disorder. This case details a young man who was hospitalized with pancytopenia due to restrictive nutritional intake related to his severe ASD. He was found to have undetectable vitamin B12 levels. His blood counts improved with transfusion, nutritional supplementation, and dental care. This report illustrates the importance of understanding ASD and potential medical complications of related behaviors.